Pengaruh Motivasi Guru dan Sarana Prasarana Sekolah terhadap Hasil Belajar Siswa di SD Negeri Se Kecamatan Rantau Bayur Kabupaten Banyuasin - Rino Hirliyanto; Yasir Arafat; Muhammad Juliansyah Putra (Mathematics Education Study Program, 2025)
The purpose of this study is to find out and describe the influence of teacher motivation and school infrastructure together on student learning outcomes at SD Negeri Se, Rantau Bayur District, Banyuasin Regency. This research was carried out in State Elementary School in Rantau Bayur District, Banyuasin Regency which consisted of 4 (two) schools including: SD Negeri 9 Rantau Bayur, SD Negeri 13 Rantau Bayur, SD Negeri 15 Rantau Bayur and SD Negeri 21 Rantau Bayur. The research method used in this study is a quantitative descriptive method. The population and sample in this study amounted to 47 teachers. Data collection techniques use observation, questionnaires and documentation. The data analysis technique used a normality test, linearity test, multicollinearity test, simple correlation analysis, multiple correlation analysis, simple regression analysis, t-test and F test. The results of this study were teacher motivation and educational infrastructure facilities - analyzed together, it was found that both had a very large influence on student learning outcomes, with a contribution of 99.2%.